Environmental laws on wildlife - Trivedi, P. R.; U K Singh (New Delhi : Ashish Pub. House and Indian Institute of Ecolocy & Environment, 1996)
Contributed research papers.
Includes index.
Rashid
Keywords: Environmental policy -- India